Organizational Transformation for Digitalization Through Sustainable IT Outsourcing - A Case Study of HR and Payroll System - Heroma in Lerum Municipality - Apirajkamol, Angsusorn; Angomjambam, Niraj Singh (My University, 2017)
This thesis was carried out in the Development department of Lerum municipality, in Västra Götaland County, Sweden, as a mandatory requirement for Master’s degree in Chalmers University of Technology. The thesis was conducted from January 2017 till May 2017 by two students, one from M.Sc. International Project Management and another from M.Sc. Quality and Operations Management Course. In Sweden, getting left behind in the fast paced world of technology and digital systems, is a source of worry. The Swedish government feels the need to use ICT and digital systems to achieve growth, better social welfare, democracy and climate improvement. However, considerable power to achieve the digital agenda lies with the Swedish municipalities. In Lerum municipality, there is also an increased drive to digitalize systems to make work and public service more efficient. However, previous experiences with digitalization projects has led to some discontentment, one such case is Heroma project. The Heroma project was the first payroll system outsourcing project, taken up by a Swedish municipality. The project outcome in terms of setting up the new system was a success, but the project implementation was not. The project was over budget and there were grievances among the employees regarding the system. Among the chaos of maintaining routine work and lost expertise in payrolls, the sustainability of the outsourced payroll system was in big question. This provided an excellent opportunity for a thesis study, to explore what leads to the success and to lay foundations for future successful IT outsourcing and its sustainability in the Swedish public sector organizations. The Heroma case was analyzed with frameworks by Moon et al. (2016) and (Duhamel et al., 2014), to check critical success factors for IT outsourcing in the public sector. Also, the Kotter’s eight steps for a successful change (Kotter, 1995), along with project management steps (PMI, 2013), to analyze any general weakness with the change initiative in the project. The other cases studied were: Heroma system used under license in Laholm municipality, payroll and IT system in SOLTAK AB and Agresso system in Lerum. All these cases were used to triangulate data, compare or find alternative solutions to same issues found in Lerum municipality. The problems with the Heroma project in Lerum municipality, were generated by data collection through surveys, interviews, observations and documentation. After which, solutions were discussed, ending with talks on sustainability of outsourced IT systems in Swedish public sector. Recommendations were given for the sustainability of outsourced IT systems in Lerum municipality, in the end. The thesis resulted in bringing Lerum municipality to a higher level of awareness regarding their organization and set a base for success of future IT outsourcing projects. The major focuses are onto the public policy and leadership, organizational strategy, procurement and contract, partnership and knowledge transfer.
Keywords: Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics; Transport